2008
DOI: 10.1126/science.1165044
|View full text |Cite
|
Sign up to set email alerts
|

Direct Imaging of Reconstructed Atoms on TiO 2 (110) Surfaces

Abstract: Determining the atomic structures of oxide surfaces is critical for understanding their physical and chemical properties but also challenging because the breaking of atomic bonds in the formation of the surface termination can involve complex reconstructions. We used advanced transmission electron microscopy to directly observe the atomic structure of reduced titania (TiO2) (110) surfaces from directions parallel to the surface. In our direct atomic-resolution images, reconstructed titanium atoms at the top su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
118
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(126 citation statements)
references
References 21 publications
7
118
0
1
Order By: Relevance
“…On the other hand, Shibata et al [13], using advanced transmission electron microscopy (TEM) observations reported results that are consistent with a different model, proposed by Park et al [12], for which the additional unit is "Ti 2 O". The main difference between the Onishi-Iwasawa and Park et al models (Onishi and Park models, respectively, in what follows) is the locations of Ti interstitial sites on the surface [13] (see Fig. 1).…”
supporting
confidence: 56%
See 2 more Smart Citations
“…On the other hand, Shibata et al [13], using advanced transmission electron microscopy (TEM) observations reported results that are consistent with a different model, proposed by Park et al [12], for which the additional unit is "Ti 2 O". The main difference between the Onishi-Iwasawa and Park et al models (Onishi and Park models, respectively, in what follows) is the locations of Ti interstitial sites on the surface [13] (see Fig. 1).…”
supporting
confidence: 56%
“…Upon thermal annealing or ion bombardment TiO 2 (110)-(1×1) surface is reduced by loosing the bridging oxygens, and is often undergo a (1×2) reconstruction with row formations [3][4][5][6][7][8][9][10][11][12][13]. The identification of these rows on reconstructed surfaces, in three dimensions, is difficult by experimental methods [13]. The best candidate for modeling this reconstruction involves the addition of "Ti 2 O 3 " molecule on the surface unit cell (added-row model) proposed by Onishi and Iwasawa [3].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This approach has led to the discovery of spherical carbon onions resulting from electron irradiation of graphitic soot, 21 the observation of the nucleation and growth of diamonds inside carbon onions under electron irradiation, 22 and more recently, the observation of reconstructions in ͑110͒ surfaces of an ultrathin TiO 2 films processed by ion beam thinning. 23 For this reason, we employed the controlled electron irradiation using transmission electron microscopy ͑TEM͒ to investigate the stability and structural changes of hexagonal MnO 2 monolayer sheets suspended on holey carbon films without any further substrate support. The study reveals atomic reconstructions under the electron-beam irradiation, resulting in new ordered domains within the MnO 2 sheets which are stable over 2 h of irradiation.…”
mentioning
confidence: 99%
“…Moreover, combination of crosssectional HRTEM observations with several kinds of different incident beam directions, enable us to three-dimensionally characterize surface structures in atomic-scale. 10) However, cross-sectional TEM is involved in intrinsic difficulty in preparing clean surfaces. In case of ceramic materials, an Ar + ion beam thinning procedure is usually utilized to make specimen transparent for electron beam at the final stage of TEM sample preparation.…”
Section: )7)mentioning
confidence: 99%